Penyuluhan dan Pemeriksaan Kesehatan sebagai Upaya Deteksi Dini Penyakit Degeneratif di Masjid Al-Mansyur Kampung Tua Belian Batam Kota - Victor E.D. Palapessy; Irma Fitrilia; Rini Susanti; Mifthahul Jannah; Deasy Ovi Harsachatri; Riska Dwi Putri; Rosi Esa Gustina; Lena Aprilia; Adella Anzalna (Jurnal Pengabdian Masyarakat, 2026)
Degenerative diseases are still a public health problem because many cases of hypertension, diabetes mellitus, and metabolic disorders are detected at an advanced stage due to low periodic health checks. This Community Service activity aims to increase public awareness about the importance of early detection of degenerative diseases through counseling and integrated health checkups. The activity was held on May 16, 2026 at the Al-Mansyur Mosque RT 03/RW 02 Kampung Tua Belian Batam City with a total of 62 participants from RT 01 to RT 04 RW 02. All participants participated in health counseling and basic examinations including blood pressure, blood sugar, uric acid, and blood type. Data was collected through observation, documentation, recording of examination results, and participant enthusiasm questionnaires, then analyzed descriptively. The average age of the participants was 45.2 ± 12.6 years, consisting of 28 males (45.2%) and 34 females (54.8%). The results of the examination showed that 24 participants (38.7%) had abnormal blood pressure, 18 participants (29.0%) had abnormal blood sugar levels, and 15 participants (24.2%) had abnormal uric acid levels. The average enthusiasm score of participants was 4.5 ± 0.4 in the high category. These findings show that religious community-based activities in mosques are effective in increasing public awareness of routine health check-ups and can be a promotive and preventive model that can be replicated in other communities.